Study on Developmental- Behavioural Pediatrics Training Experiences of Pediatricians and Pediatric Trainees Working in Nepal - Rimal, HS; Pokharel, A; Saha, V (Kathmandu University Medical Journal, 2015)
Background There are growing concerns about developmental, behavioural, social and emotional wellbeing of children throughout the world. A huge gap exists between the instructions provided on medical disciplines and on areas of Developmental- Behavioural Pediatrics (DBP) during pediatric training in our region. Objective This study aims to evaluate the Developmental –Behavioural pediatrics (DBP) training experiences of pediatricians and pediatric trainees during their post graduate training in pediatrics. Methods Questionnaires were sent to the pediatricians / trainees and data was analyzed using SPSS software. Result More than 56 % of respondents were satisfied in 10 out of 11 medical disciplines where as more than 56% were unsatisfied in 10 out of 11 developmental behavioural pediatrics disciplines. This Study has demonstrated that between 50-60 % of pediatricians did not see the cases of ADHD, Learning difficulty and family dysfunction for a period of three months prior to the survey which are relatively common conditions. Even in post graduate training nearly 66 % of pediatricians were unsatisfied with their instructions in DB pediatrics. Conclusion Pediatricians working in Nepal have difficulties in addressing the issues of developmental pediatrics, raising a question about the need to review the curriculum of post graduate training in Pediatrics. DOI: http://dx.doi.org/10.3126/kumj.v11i3.12502 Kathmandu Univ Med J 2013; 43(3):191-195